Dinamika Politik Hukum Batasan Usia Perkawinan di Indonesia: Antara Norma Agama dan Perubahan Sosial - Kafidhoh, Siti; Asyari, Nadzif Ali; Ali Mutakin, Ali Mutakin; Saujan, Iqbal (Jurnal Hukum Islam, 2024)
The change in regulations regarding the age limit for marriage in Indonesia is a response to the high rate of child marriage, which still faces various challenges in its implementation. This study examines the debate between tradition and modernity in child marriage practice, the legislative process, and the challenges faced in changing the age limit norms for marriage and marriage dispensation as a legal loophole in enforcing the age limit norms for marriage. The research method employs a normative juridical with statutory and conceptual approaches. The study results show that changes in the age limit norms for marriage aimed to protect children's rights. However, religious norms and social pressure influence its implementation through marriage dispensation in the Religious Court, resulting in inconsistencies in its law enforcement. This condition poses a challenge to harmonize religious norms with social change. This study emphasizes the need for a more transparent and strict marriage dispensation mechanism. In addition, increasing public legal awareness is the key to encouraging social changes that support child protection. Strengthening public awareness and consistent regulations is expected to minimize and suppress the number of child marriages.